Tumor factors associated with in‐field failure for nasopharyngeal carcinoma after intensity‐modulated radiotherapy. Issue 4 (24th January 2022) - Liu, Xixi; Wu, Bian; Huang, Jing; Qin, You; Zhang, Zhanjie; Shi, Liangliang; Hong, Xiaohua; Ding, Qian; Peng, Gang; Yang, Kunyu
Abstract: Background: To identify the tumor factors of in‐field failure for nasopharyngeal carcinoma (NPC) in the intensity‐modulated radiotherapy (IMRT) era. Methods: Patterns of recurrence were classified as in‐field, marginal, and out‐field failures. Multivariate analyses with the Cox proportional hazards model were used to identify tumor‐related factors of in‐field failure. Results: A total of 1039 patients with NPC received IMRT from 2012 to 2019 and 75 developed recurrences, with 88.0% (66/75) considered as having in‐field failures. Multivariate analysis showed that pretreatment gross tumor volume of nasopharynx ≥68.8 mL and histopathological type of nonkeratinizing differentiated carcinoma (NKDC) were the independent tumor factors of in‐field local failure, while gross tumor volume of involved lymph nodes ≥19.9 mL and cervical nodal necrosis (CNN) were associated with in‐field regional failure (all p < 0.05). Conclusions: In‐field failure was the major pattern of recurrence in patients with NPC. Large tumor volume, NKDC, and CNN were the tumor factors associated with in‐field failure.